Norwegian Rural Vigilantism during COVID-19: Self-Protection against a Perceived Urban Threat - Vestad, Maja (International Journal of Rural Criminology, 2023)
When private citizens mobilise to protect their local community against threats, the rationale is that the local government is unable or unwilling to do so, due to legal restrictions, a lack of organisational resources and capacity – or indifference and discrimination. While these practises are commonly theorised as vigilantism, this conceptual approach draws in large part on studies of urban parts of the United States, Latin/South America, and the Commonwealth countries. This corresponds to a parallel knowledge gap in rural criminology, where there is little knowledge of so-called peripheral areas in the global north as well as a dearth of theoretical conceptualisation about rural vigilantism, and few studies cover areas outside the Anglo-American context. Drawing on qualitative fieldwork in 2020, this paper contributes to knowledge of vigilantism in the Nordics by providing a study on how Norwegian citizens mobilised to protect local communities from an urban pandemic threat, constituting a new form of rural vigilantism.